2004
DOI: 10.1242/jcs.00970
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human embryonic stem cell differentiation by BMP-2 and its antagonist noggin

Abstract: Human embryonic stem cells differentiate spontaneously in vitro into a range of cell types, and they frequently give rise to cells with the properties of extra-embryonic endoderm. We show here that endogenous signaling by bone morphogenetic protein-2 controls the differentiation of embryonic stem cells into this lineage. Treatment of embryonic stem cell cultures with the bone morphogenetic protein antagonist noggin blocks this form of differentiation and induces the appearance of a novel cell type that can giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
322
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(350 citation statements)
references
References 36 publications
25
322
0
3
Order By: Relevance
“…Human stem and progenitor cell control by the TGF-b superfamily has been extensively studied in vitro with various cell types such as hHSCs, [25][26][27][28] keratinocytes, 29 and more recently, human adult embryonic stem cells (hESCs). [47][48][49][50][51][52][53] Our preliminary study of the effect of TGF-b on MSCs (data not shown) also indicates that blocking TGF-b can activate a subpopulation of highly proliferative progenitor cells. Interestingly, however, the simultaneous addition of neutralizing antibodies for TGF-b and IFN had no additive effect, suggesting that both treatments activated similar cell subpopulations.…”
Section: G12mentioning
confidence: 77%
“…Human stem and progenitor cell control by the TGF-b superfamily has been extensively studied in vitro with various cell types such as hHSCs, [25][26][27][28] keratinocytes, 29 and more recently, human adult embryonic stem cells (hESCs). [47][48][49][50][51][52][53] Our preliminary study of the effect of TGF-b on MSCs (data not shown) also indicates that blocking TGF-b can activate a subpopulation of highly proliferative progenitor cells. Interestingly, however, the simultaneous addition of neutralizing antibodies for TGF-b and IFN had no additive effect, suggesting that both treatments activated similar cell subpopulations.…”
Section: G12mentioning
confidence: 77%
“…Spinal cord neurogenesis is promoted by inhibition of BMP signaling through expression of Noggin (Setoguchi et al, 2004). Extraembryonic endodermal fate of stem cells is inhibited and neuronal precursor fate is induced in other experimental systems by similar inhibition of signaling by BMP2 using noggin expression (Pera et al, 2004). Two reports suggest that specific precursors could turn towards astrocytic lineage under the influence of BMP or TGF-b: cerebellar granule cell precursors that express GFAP and S100 under the influence of BMP2 (Okano-Uchida et al, 2004), and astrocytic precursors that are induced to express cystatin C by TGF-b (Kumada et al, 2004).…”
Section: Tgf-b and Neural Stem Cells (Nscs)mentioning
confidence: 99%
“…Hence, comparing their differentiation potentials and response to specifi c signaling molecules is still required to allow drawing conclusions on whether hESCs and iPSCs show critical differences. It was previously shown in hESCs that the bone morphogenetic protein inhibitor noggin induces neuroectodermal differentiation, as shown by the expression of SOX2, paired box protein 6, and nestin and a lack of expression of early mesoderm or endoderm markers ( 10 ). Once dissected, these colonies are propagated in suspension in neural basal media (NBM) supplemented with basic fi broblast growth factor (bFGF) and epidermal growth factor (EGF), where they aggregate and form a spherical-like cluster named neurosphere, which consists of a heterogeneous population of NS/PCs ( 10 ).…”
mentioning
confidence: 99%
“…It was previously shown in hESCs that the bone morphogenetic protein inhibitor noggin induces neuroectodermal differentiation, as shown by the expression of SOX2, paired box protein 6, and nestin and a lack of expression of early mesoderm or endoderm markers ( 10 ). Once dissected, these colonies are propagated in suspension in neural basal media (NBM) supplemented with basic fi broblast growth factor (bFGF) and epidermal growth factor (EGF), where they aggregate and form a spherical-like cluster named neurosphere, which consists of a heterogeneous population of NS/PCs ( 10 ). Neurospheres can be differentiated to give rise to neurons and glia when plated onto laminin or fi bronectin substrates, respectively.…”
mentioning
confidence: 99%